Sharia and the Muslim Diaspora - Rohe, Mathias (The Ashgate Research Companion to Islamic Law, 2014)
Per the extremist view, Sharia in the diaspora is either indispensable-cf., for example, Sharia4Belgium1 and Sharia4Holland,2 two Muslim groups explicitly rejecting Belgian and Dutch democratic systems respectively-or the biggest danger for Western values-cf. the slogan Maria statt Scharia (Maria instead of Sharia) of the right-wing, populist, and anti-Islamic Swiss People’s Party (SVP) in the 2009 electoral campaign.3 But what do they mean by the use of “Sharia”?.
UnivIS-Import:2015-04-20:Pub.2014.rw.recht.IZZ.LZZA.sharia